FULFILLMENT OF THE POLITICAL RIGHTS OF PERSONS WITH DISABILITIES FROM A CONSTITUTIONAL SCIENCE PERSPECTIVE: A CONSTITUTIONAL ANALYSIS OF SOCIAL, CULTURAL, AND POLITICAL DISCRIMINATION IN INDONESIA - Fenty Widya,; Heni Susanti,; Apriansyah, (Proceeding International Conference on Social Sciences, 2026)
This research examines the fulfillment of political rights for persons with disabilities from the perspective of constitutional law, focusing on constitutional analysis of social, cultural, and political discrimination experienced by this group in Indonesia. Despite the 1945 Constitution of the Republic of Indonesia guaranteeing universal political rights to all citizens without exception, including persons with disabilities, the reality on the ground shows various forms of denial of the principle of equality before the law and government. Conceptually, the state has a constitutional obligation to protect, respect, and fulfill these rights, especially within the framework of a democratic state that upholds human rights. This research uses a normative-juridical and socio- constitutional approach with descriptive qualitative methods based on document studies, case analysis, and participatory observation of election implementation and political accessibility in various regions. The main findings show that the implementation of political rights for persons with disabilities still faces systemic barriers, such as inaccessible polling stations, inaccessible political information (especially for the blind, deaf, and intellectually disabled), and low involvement of political parties in promoting disability candidates. This is exacerbated by cultural stigma that views persons with disabilities as incapable, unworthy, and unimportant in public decision-making. This discrimination is not only social but also institutionalized in the political process. From the perspective of constitutional law, this condition reflects the state's failure to implement the principle of inclusive constitutionalism. Therefore, the state must fulfill positive obligations through affirmative policies, legal reform, and strengthening independent human rights institutions. This research highlights the importance of integrating disability rights into the structure of constitutional law norms, including through judicial review and the formation of new norms based on the Convention on the Rights of Persons with Disabilities (CRPD). Furthermore, this research proposes the establishment of an independent Regional Disability Commission with a mandate to oversee the implementation of political rights for persons with disabilities. Collaboration between disability organizations, academics, and the government is key to achieving structural reform in the national political system. The fulfillment of political rights for persons with disabilities must be a primary parameter of the Indonesian state's success in eliminating discrimination and ensuring social justice for all citizens.